Formulation And Physical Stability Test Of Mother-In-Law’s Tongue Leaves Extract Lotion As An Antioxidant - Lela Mukmilah Yuningsih; Dikdik Mulyadi; Siti Inayah; Sita Sopatul Marwah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Mother-in-law's tongue leaves (Sansevieria trifasciata P.) is a plant of the genus Sansevieria with flavonoid compound namely trifasciatin, as an antioxidant. Antioxidants can be used in cosmetics to protect the skin from free radicals. The purpose of this research was to analyze antioxidant activity of mother-in-law's tongue leaves extract and to obtain the best lotion formulation with various concentrations. Samples were extracted using 96% ethanol solvent with maceration method. Antioxidant activity was tested using DPPH method and intensity was measured at λ=517 nm by UV-Vis spectrophotometer. The IC50 value=49.72 ppm indicates a very strong antioxidant activity, compared to vitamin C=4.01 ppm (very strong). Extract was formulated in lotion with various concentrations of 0.5%, 1%, 3%, 6% and the comparison was vitamin C with same concentration as well as base without the addition of active substances. Based on observations for 4 weeks, 3% extract lotion is the best formulation. The organoleptic test results showed no change in shape, texture, color, odor, and pH so lotion was stable. In addition, the value of viscosity, spreadability, adhesion, irritation test according to established standards also has an antioxidant value 99.72% (strong category). So effective to ward off free radicals on the skin.